L'écriture comme analyseur des tensions identitaires dans une formation professionnalisante à l'université - Valérie Guillemot; Michel Vial (Presses universitaires de la Méditerranée, 2012)
This research communication shows how a professionnalizing and graduating vocational training programm in an University's Educational Science's department leads to stress and accelerate change in one's identity evolution. This article intends to show how written academic study works contribute to increase the speed of such a change. Either set or volontary study work could play a part in persuit of identity and identity linkage.